A bankruptcy approach to support decisions on allocation of scarce resources in emergency operations. (2017) - Itani, Maher N.; Shakya, Sumadhur
It is essential for humanitarian organisations to develop fair allocation guidelines of scarce lifesaving resources that alleviate the suffering of beneficiaries. At the same time, it is challenging to set a rationality behind the resources allocation and toward which beneficiaries to aid. This study examines resource allocation decisions using a bankruptcy based framework. It focuses on carrying out set rules in a fair manner so that a just outcome might be reached. Choosing which rule is most appropriate is challenging as this depends on how the decision makers understand the particular circumstances of each allocation situation. Still, these presented allocation rules provide the most flexible, efficient, and defensible solutions to equitable resource allocation. Furthermore, these schemes do not require detailed knowledge of beneficiaries' utilities for resources, which is generally not feasible to obtain during disaster circumstances.